2016
DOI: 10.1002/2016rs006098
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of thermospheric measurements for ionosphere‐thermosphere state estimation

Abstract: We develop a method that uses data assimilation to estimate ionospheric‐thermospheric (IT) states during midlatitude nighttime storm conditions. The algorithm Estimating Model Parameters from Ionospheric Reverse Engineering (EMPIRE) uses time‐varying electron densities in the F region, derived primarily from total electron content data, to estimate two drivers of the IT: neutral winds and electric potential. A Kalman filter is used to update background models based on ingested plasma densities and neutral wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 32 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…For this reason tracer trajectories appear to cross the LCS ridges. In addition, using data assimilation drifts from methods such as Estimating Model Parameters from Ionospheric Reverse Engineering (EMPIRE; Miladinovich et al, 2016) and Super Dual Auroral Radar Network (SuperDARN; Ruohoniemi et al, 1989) could provide data-driven plasma drifts that could be used as the inputs to ITALCS in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason tracer trajectories appear to cross the LCS ridges. In addition, using data assimilation drifts from methods such as Estimating Model Parameters from Ionospheric Reverse Engineering (EMPIRE; Miladinovich et al, 2016) and Super Dual Auroral Radar Network (SuperDARN; Ruohoniemi et al, 1989) could provide data-driven plasma drifts that could be used as the inputs to ITALCS in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The correction to the field‐parallel drift δv || in Equation 2 is estimated as due strictly to projections of the horizontal geographic meridional and zonal components of the neutral wind δu N and δu E , respectively, onto the field‐aligned direction. Each is fit to its own power series basis functions (Miladinovich et al, 2016), for example, δu N as shown below: δvfalse|false|=δufalse|false|=δuNtruen^·trueb^+δuEtruee^·trueb^ δuNfalse(r,θ,ϕfalse)=truek=0kmaxtruel=0lmaxtruep=0pmaxxklp)(rRekfalse(θθ0false)lfalse(ϕϕ0false)p where truen^ is a unit vector pointing toward geographic north, truee^ geographic east, and trueb^ along the field line. We assume that there is negligible vertical wind motion.…”
Section: Overview Of the Empire Algorithmmentioning
confidence: 99%
“…The correction to the field-parallel drift 𝛿v || in Equation 2 is estimated as due strictly to projections of the horizontal geographic meridional and zonal components of the neutral wind 𝛿u N and 𝛿u E , respectively, onto the field-aligned direction. Each is fit to its own power series basis functions (Miladinovich et al, 2016), for example, 𝛿u N as shown below:…”
Section: Overview Of the Empire Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how energy and momentum are transferred through the generation, propagation, and dissipation of atmospheric waves over a wide range of spatial and temporal scales is one of key factors to understand the variability of the T/I system [20]. Connecting the dynamics of the neutral atmosphere and the ionosphere improves the modelling and forecasting capabilities (see, e.g., [13,19,20,24]. Observing gravity waves in the middle atmosphere at high spatial resolution will also contribute to improving global and regional climate projections and sub-seasonal weather forecasts (10-30 days) due to the downward coupling of these waves.…”
Section: Introductionmentioning
confidence: 99%